2021
DOI: 10.1021/acsami.1c16612
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of a 3D Hollow BiOBr@Bi-MOF Heterostructure with Enhanced Photocatalytic Degradation of Dyes

Abstract: Considering the flexibility, adjustable pore structure, and abundant active sites of metal–organic frameworks (MOFs), rational design and fine control of the MOF-based hetero-nanocrystals is a highly important and challenging subject. In this work, self-assembly of a 3D hollow BiOBr@Bi-MOF microsphere was fabricated through precisely controlled dissociation kinetics of the self-sacrificial template (BiOBr) for the first time, where the residual quantity of BiOBr and the formation of Bi-MOF were carefully regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(78 citation statements)
references
References 50 publications
5
73
0
Order By: Relevance
“…The kinetic equation is given below. 70,71 where the initial Cr( vi ) concentration is C 0 , the final Cr( vi ) concentration is C t at time t , and the pseudo-first-order rate constant is k . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The kinetic equation is given below. 70,71 where the initial Cr( vi ) concentration is C 0 , the final Cr( vi ) concentration is C t at time t , and the pseudo-first-order rate constant is k . Fig.…”
Section: Resultsmentioning
confidence: 99%
“…After illumination of 5 min, an obvious EPR four-component signal was observed, corresponding to the peak of DMPO–˙O 2 − , which suggested that the ˙O 2 − radicals were crucial to CIP degradation in the photocatalytic system, consistent with the results of the trapping experiments. It is noted that h + , ˙O 2 − and e − are involved in the photocatalytic degradation of CIP; h + , ˙O 2 − are the dominant active species in the photocatalytic degradation of RhB, 42 while ˙O 2 − is the main active species for MB and the surface hydroxyl group is efficient for phenol removal. 43,44 Thus, it can explain why the degradation rates of CIP and RhB are higher than that of MB and phenol because of different active species and surface charges.…”
Section: Resultsmentioning
confidence: 99%
“…− and e − are involved in the photocatalytic degradation of CIP; h + , ˙O2 − are the dominant active species in the photocatalytic degradation of RhB, 42 while ˙O2 − is the main active species for MB and the surface hydroxyl group is efficient for phenol removal. 43,44 Thus, it can explain why the degradation rates of CIP and RhB are higher than that of MB and phenol because of different active species and surface charges.…”
Section: Degradation Mechanismmentioning
confidence: 99%
“…3f; the ternary heterostructure possessed much higher N 2 uptake and specific surface area (S BET ) than that of g-C 3 N 4 , which was favorable to the improvement of the photocatalytic activity. 16,[37][38][39] The photocatalytic hydrogen production activities of g-C 3 N 4 and its heterostructures were tested under visible light irradiation and systematically compared in Fig. 5 to reveal the important synergistic effect of PPy and Fe 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%